Money Demand Function for Nepal: An Empirical View from Expenditure Component - Adhikari, Pujan (Economic Journal of Development Issues, 2019)
This paper examines the long run and short-run dynamics relationship between broad money, consumption expenditure, capital stock and interest rate in Nepal over the period of 1975-2017. This paper employs ARDL bound testing approach for co-integration between the broad money demand and its determinants. Result reveals the evidence of cointegration among the variables. The empirical results show that the demand for money is affected by the interest rate and final consumption expenditure both in the long run and short-run. However, the gross fixed capital formation has no impact on demand for money in the long-run and short-run as well. On contrast, interest rate is positively associated with Broad money demand, which is not consistent with theoretically. Positive association of money demand with interest rate shows that demand for money function is instability in Nepal. Thus, this study suggests that policy maker to correct price fluctuation through the control of various expenditure components, particularly, real final consumption expenditure might be an important strategy in the long run. However, the gross fixed capital formation has no impact on demand for money in the long-run.